Investigating the Alignment Between English Language Arts Curricula Developed for Students With Significant Intellectual Disability and the CCSS. (September 2020) - Taub, Debbie; Apgar, Jessica; Foster, Megan; Ryndak, Diane Lea; Burdge, Michael D.; Letson, Sarah
Federal law requires all students, including those with significant intellectual disability, to make progress toward grade-level general education standards. The alignment between standards, curriculum, and instruction is vital for ensuring equitable opportunities to learn. Commercially available curricula attempt to support teachers and students by aligning instructional materials to standards, but few studies exist to verify this alignment. Those that have been conducted for general education curriculum have not been promising. This study uses the Links for Academic Learning protocol to evaluate the alignment of curricula designed for students with significant intellectual disability (SWSID) that mark themselves as aligned to grade-level standards. Findings related to the alignment between the standards, lesson objectives, and lesson content are reported. The researchers discuss implications related to the adoption and use of curricula specifically designed for SWSID and the need for additional research in this area.